2022
DOI: 10.36680/j.itcon.2022.035
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of virtual reality in construction education: a content-analysis based literature review

Abstract: In construction education many research initiatives have explored the adoption of innovative and interactive learning experiences for improving the visual, analytical and problem-solving skills of students. Virtual reality (VR), in particular, has been increasingly viewed as a promising way for students to dynamically interact with information, to test concepts in a visual and intuitive manner and, through real-time feedback, to begin to construct their knowledge and spatial skills. However, with the prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…The results of their study showed that students could find a higher number of design mistakes when performing design reviews in VR compared to reviewing physical construction drawings. Mastrolembo Ventura et al (2022) emphasized that VR-based games are more effective than traditional instruction because they allow students to fail, but the in-process reflection enables them to modify their strategies and repeat the process until they reach their goals. Tennakoon et al (2023) developed a VR sandbox to provide students with hands-on experience for exploring complex geological features that make up well-known terrains.…”
Section: Vr In Aec Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of their study showed that students could find a higher number of design mistakes when performing design reviews in VR compared to reviewing physical construction drawings. Mastrolembo Ventura et al (2022) emphasized that VR-based games are more effective than traditional instruction because they allow students to fail, but the in-process reflection enables them to modify their strategies and repeat the process until they reach their goals. Tennakoon et al (2023) developed a VR sandbox to provide students with hands-on experience for exploring complex geological features that make up well-known terrains.…”
Section: Vr In Aec Educationmentioning
confidence: 99%
“…Despite the past efforts in developing educational VR applications for the AEC industry, conceptual and empirical challenges for the justification of these applications from the pedagogical, methodological, and theoretical perspectives still exist (Mastrolembo Ventura et al 2022). According to their study, since 2001 only 40% of studies in VR implementation in AEC education declared a sample size and most studies did not leverage validated assessment instruments.…”
Section: Vr In Aec Educationmentioning
confidence: 99%
“…Most virtual reality (VR) simulations in education are used for design visualisation (Castronovo et al, 2020;Nikolic & Windess, 2019), construction safety education (Le et al, 2015;Sacks et al, 2013), equipment operation, and structural analysis (Abdelhameed, 2013). Therefore, due to contextual variations and their unique features, educational VR applications still fall short of offering straightforward VR solutions to consistently realise the benefits mentioned above, revealing a plethora of conceptual and empirical challenges in how VR is conceptualised and justified in construction education from the pedagogical, methodological, and theoretical perspectives (Ventura et al, 2022). The utilisation of virtual reality in remote communication applications has been demonstrated to achieve better co-presence and shared emotional understanding compared to artificial user avatars (Li et al, 2019;Smith & Neff, 2018).…”
Section: Education and Communicationmentioning
confidence: 99%